Equity Planning Outside City Hall: Rescaling Advocacy to Confront the Sources of Urban Problems. (September 2015) - Doussard, Marc
Focusing on progressive economic development policy and the institutional form of the community–labor coalition—an alliance between labor unions and urban advocacy organizations—this article assesses the potential to scale equity planning "up" to political scales at which redistributive policy is both more effective and more likely to be enacted. I investigate when and why scaling up works through a comparison of two differently scaled campaigns to raise wages in Chicago's service industries. The results indicate that equity planners in City Hall can expand their ability to address structural economic problems by allying with nationally organized activist organizations.